Tracks in the Snow – Advantage of Combining Optical Methods to Characterize Marine Particles and Aggregates - Markussen, Thor N.; Konrad, Christian; Waldmann, Christoph; Becker, Marius; Fischer, Gerhard; Iversen, Morten H. (Frontiers in Marine Science, 2020)
Settling marine aggregates, such as zooplankton fecal pellets and marine snow, transport organic matter from the surface ocean to the deep sea and are largely responsible for the ocean’s sequestration of carbon. However, our understanding of the functioning of the biological pump and the distribution of particulate organic matter in the water column often hinge on limited bulk data from sediment traps, large volume filtration or instantaneous snap-shots from in situ optical systems that only see a small part of the particle and aggregate spectra. We evaluated the added value of combining different optical systems to detect a range of organic and inorganic particle types during a case-study in the Cape Blanc upwelling region. Laboratory calibrations showed that one camera system detected large organic aggregates well and in situ data showed that it correlated positively with fluorescence. The other camera was better at detecting small, mainly inorganic particles which were not seen by the first camera and correlated positively with turbidity. The combined deployments of the two optical systems together with fluorescence and turbidity sensors showed potentials for added insights into spatial (depth) and temporal (diurnal) particle dynamics. The case study exemplified the different efficiencies of two camera systems to detect particles of different types in marine waters. From this, the results highlighted the importance of discriminating between qualitative and quantitative ranges of imaging systems, in order to understand the quantitative range of sizes as well as types of particles detected by a given system. This is especially important when optical systems are used to estimate carbon fluxes and particulate organic matter distribution in the water column from vertical profiles of particle size-distribution and abundance.